Incidence and risk factors for surgical site infection post-gynecological operations in a tertiary hospital in Egypt: a retrospective study - Goma, Khaled; Gelany, Saad El; Galal, Ahmed Fawzy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Surgical site infection (SSI) is the most common complication of surgical procedures in gynecology and it poses a significant burden for both patients and healthcare systems. Our objective was determining the incidence and risk factors for SSI post-gynecological operations during the period of five years. Methods: A matched case-control study at Minia maternity university, Egypt where A total of 18772 cases had undergone different gynecological procedures. The 876 cases were complicated with SSI (SSI cases group) and 2 matched controls per case were chosen from the rest of the cases and served as the control group (n=1752 cases). Results: The overall incidence of SSI post-gynecological operations was 4.67% and post-hysterectomy was 7.57%. SSI group had a significantly higher number of cases with diabetes, obesity, high parity (>4), increased blood loss and those had prolonged duration of surgery compared to the control group (all p<0.01). Conclusions: The identified risk factors are crucial for risk stratification of SSI and prioritizing interventions to improve the outcome. These results could give a picture for SSI post-gynecological operations in our country and identifying these risk factors is crucial for risk stratification of SSI and prioritizing interventions to improve the outcome.